The Effect of High Nitric Oxide Concentrations on Oxygenators in Cardiopulmonary Bypass Machines (Experimental Study) - A. M. Radovskiy; I. V. Vorotyntsev; A. A. Atlaskin; A. N. Petukhov; S. S. Kryuchkov; M. E. Atlaskina; A. N. Stepakova; A. O. Marichev; E. K. Barygin; V. V. Osovskikh; V. D. Selemir; S. N. Buranov; et al. (Общая реаниматология, 2024)
The aim of the study. To study the effect of high nitric oxide concentrations on hollow polypropylene fibers of oxygenators.Materials and methods. The study was conducted in two stages. At the first stage, we evaluated the stability of oxygenator membrane made of hollow polypropylene fibers after six hours of exposure to air-oxygen mixture containing NO at 500 parts per million, or 500 pro pro mille (ppm) concentration, using mass spectrometry and infrared spectroscopy. At the second stage, an experiment with cardiopulmonary bypass (CPB) was conducted on 10 pigs. In the study group (n=5) animals sweep gas was supplied to the oxygenator as an air-oxygen mixture with NO at 100 ppm. In the control group animals (n=5) an air-oxygen mixture was used without NO. The CPB lasted for 4 hours, followed by observation for 12 hours. NO, NO2 (at the inlet and outlet of the oxygenator), and the dynamics of methemoglobin were evaluated. After weaning of animals from CPB, the oxygenators were tested for leakproofness, and scanning electron microscopy (SEM) was performed.Results. The oxygenator made of polypropylene hollow fibers retained its gas transfer parameters after six hours of exposure to air-oxygen mixture containing NO at 500 ppm. Based on IR-Fourier spectroscopy findings, NO did not affect structural integrity of polypropylene membranes. NO added to gas mixture at 100 ppm did not increase NO2 to toxic level of 2 ppm in 91% of control tests during 4 hours CPB in pigs; mean value was 1.58 ± 0.28 ppm. Methemoglobin concentration did not exceed the upper limit of permissible level (3%), and there were no statistically significant differences with the control group. All tested oxygenators have passed the leakproofness test. According to SEM findings, larger amounts of fibrin deposits were found in the control group oxygenators vs study group.Conclusion. There were no negative effects of NO at 500 ppm concentration on the oxygenator membrane made of hollow polypropylene fibers. NO at 100 ppm in a gas-mixture supplied to oxygenators did not lead to an exceedance of safe NO2 and methemoglobin concentrations in an animal model. Reduced fibrin deposits on hollow fibers of polypropylene oxygenator membranes were observed when with NO at a level of 100 ppm was added to a gas mixture.